Meningkatkan Kemampuan Pemecahan Masalah Matematik dan Self Efficacy Siswa SMP Menggunakan Pendekatan Contextual Teaching and Learning - devi gustia; jenab hanifah (IKIP Siliwangi, 2019)
This study aimed to determine the improvement of mathematical problem solving abilities and self efficacy students of Junior High School through the Contextual Teaching and Learning approach. The method of this research is the quasi-experimental method with the research design of the post-test control group design. The population in this study was the seventh grade of SMPN 1 TelukJambe Barat City of Karawang. Determination of the sample is done by the technique used which is not random so the class selected as the experimental class is class VII D and VII A as the control class. Instruments given to students in the form of test questions (pretest-posttest) related to indicators of mathematical problem solving abilities. Analysis of data processing was carried out on the results tests of mathematical problem solving abilities of students at SMPN 1 TelukJambe Barat. To get the research data, the instruments were used in the form of tests (pretest-posttest) and self efficacy scale. The analysis of the study used the average difference test. The results of the study concluded: (1) Achievement and improvement of mathematical problem solving skills that are learned by using contextual teaching and learning approaches are better than students who receive learning with a scientific approach. (2) Mathematical self efficacy of students who learn to use Contextual Teaching and Learning is better than students with learning using a scientific approach.